Uses of Machine Learning in Healthcare Sectors - Abbas GulmuradBeg, Murad Wafaa Adnan Sajid (Mathematical Statistician and Engineering Applications, 2022)
When it comes to human health and life, any technology that can provide a more efficient, useful and faster analysis to deliver an appropriate treatment plan on time is of immense value. Artificial intelligence and its division M.L. It is taking over the world now every day little by little business use cases are appearing in technologies news. Industry is same withadministration or financial fields seek to be the best choices for technology, but other sectors Are the healthcare industry any different or same?Be sure not. Speaking of AI in the field of medicine, we must realize the huge potential and changes that M.L can contribute to the healthcare industry.